The ecological niche and distribution of Neanderthals during the Last Interglacial. (9th August 2016) - Benito, Blas M.; Svenning, Jens‐Christian; Kellberg‐Nielsen, Trine; Riede, Felix; Gil‐Romera, Graciela; Mailund, Thomas; Kjaergaard, Peter C.; Sandel, Brody S.
Abstract: Aim: In this paper, we investigate the role of climate and topography in shaping the distribution of Neanderthals ( Homo neanderthalensis ) at different spatial scales. To this end, we compiled the most comprehensive data set on the distribution of this species during the Last Interglacial optimum (MIS 5e) available to date. This was used to calibrate a palaeo‐species distribution model, and analyse variable importance at continental and local scales. Location: Europe and Irano‐Turanian region (20° N to 70° N, 10° W to 70° E). Methods: We used archaeological records and palaeoclimatic and topographic predictors to calibrate a model based on an ensemble of generalized linear models fitted with different combinations of predictors and weighted background data. Area under the curve scores computed by leave‐one‐out were used to assess variable importance at the continental scale, while local regression combined with recursive partition trees was used to assess variable importance at the local scale. Results: Annual rainfall and winter temperatures were the most important predictors at the continental scale, while topography and summer rainfall defined habitat suitability at the local scale. The highest habitat suitability scores were observed along the Mediterranean coastlines. Mountain ranges and continental plains showed low habitat suitability values. Main conclusions: The model results confirmed that abiotic drivers played an important role in shaping Neanderthals distribution during the Last Interglacial. The high suitability of the Mediterranean coastlines and the low suitability values of most sites at the northern and eastern distribution limits (Germany, Hungary, Ukraine) challenge the notion of Neanderthals as a species with preference for colder environments.